Pelatihan Pembukuan Sederhana Pada Pelaku UMKM di Desa Bawak Kecamatan Cawas Kabupaten Klaten - Nabila Aulia Astari; Nugraeni Nugraeni (Pusat Riset dan Inovasi Nasional, 2023)
Financial bookkeeping is very important for every business. Financial bookkeeping produces financial statement that show profit or loss from the operational activities of a business. Small, micro and medium business in Bawak Village, Cawas District, Klaten Regency do not yet know and understand accounting. The problem was identified based on the interview during the observation stage. Based on these problems, the aim of this community service activity is to provide information and understanding about simple bookkeeping through a training activity. The methods used in this community service activity are 1) Observation,2)Training,3)Evaluation. This community service activity results in the owner business understanding the importance of financial recording and financial statement.